TARAF HIDUP RUMAH TANGGA NELAYAN PENANGKAP GURITA DI DESA BULUTUI KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA PROVINSI SULAWESI UTARA - Adhiah Mella Cahyani; Siti Suhaeni; Srie J. Sondakh; Florence V. Longdong; Steelma V. Rantung (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2023)
Abstract The purpose of this study, first to find out what are the sources and how much income of octopus-catching fisherman households, secondly to find out what types and amounts of octopus-catching fisherman households spend, and thirdly to find out how the standard of living of octopus-catching fishermen is. The method used in this research is survey method. The population in this study were octopus fishermen in Bulutui Village. The data collection method used is census. The census was conducted on a total population of 38 respondents. The data collected consists of primary data and secondary data. Primary data collection was carried out through observation and interviews guided by questionnaires. Secondary data were obtained from the Bulutui Village Office and previous studies related to this research. The data analysis used is descriptive qualitative and quantitative analysis. The standard of living of octopus fishing households was analyzed using the Engel Index. Based on the research results, it is known that fishermen's household income comes from work as octopus fishermen, and side jobs are still in the field of fisheries, such as crew members. Other jobs outside the fishery sector such as being a construction worker and animal breeder. The average total household income of octopus fishermen in Bulutui Village for one year is Rp. 34.254.349. There are 2 types of expenditure for fishing households in Bulutui Village, which is expenditure for food and expenditure for non-food. The average total expenditure for one year is Rp. 34.254.349, which is divided into expenditure for food needs of Rp. 17.981.053 and expenditure for non-food needs which are Rp. 16.273.296. The results of the analysis of the Engel Index are 52,49%, meaning that more than half of the total income of octopus fishermen is used to meet food needs only. The proportion for food, which is 52,49%, is greater than the proportion for non-food, which is 47,51%. This indicates that the standard living or welfare level of octopus fishermen in Bulutui Village is still relatively low because more than half of their income is only sufficient to meet food needs. Â  Keywords: standard of living, fishermen, octopus, Bulutui. Â Abstrak Tujuan penelitian ini untuk mengetahui sumber dan jumlah pendapatan rumah tangga nelayan penangkap gurita, dan untuk mengetahui jenis dan jumlah pengeluaran rumah tangga nelayan penangkap gurita, serta untuk mengetahui bagaimana taraf hidup nelayan penangkap gurita di Desa Bulutui. Metode yang digunakan dalam penelitian ini ialah metode survei. Populasi dalam penelitian ini ialah nelayan penangkap gurita yang ada di Desa Bulutui yang berjumlah 38 orang. Metode pengambilan data menggunakan metode sensus Data yang dikumpulkan terdiri atas data primer dan data sekunder. Pengumpulan data primer dilakukan melalui observasi dan wawancara yang dipandu dengan kuisioner. Data sekunder diperoleh dari Kantor Desa Bulutui dan penelitian-penelitian terdahulu yang ada kaitannya dengan penelitian ini. Analisis data yang digunakan iaalah analisis deskriptif kualitatif dan kuantitatif. Taraf hidup rumah tangga nelayan gurita dianalisis dengan Indeks Engel. Berdasarkan hasil penelitian diketahui bahwa pendapatan rumah tangga nelayan bersumber dari pekerjaan sebagai nelayan penangkap gurita, dan pekerjaan sampingan masih dibidang perikanan, seperti ABK. Pekerjaan lain diluar bidang perikanan seperti menjadi tukang bangunan dan peternak hewan. Total pendapatan rumah tangga nelayan penangkap gurita di Desa Bulutui rata-rata per tahun adalah Rp. 34.254.349. Pengeluaran rumah tangga nelayan di Desa Bulutui ada 2 macam, yaitu pengeluaran untuk pangan dan pengeluaran untuk non pangan. Total pengeluaran rata-rata per tahun adalah sebesar Rp. 34.254.349 yang terbagi menjadi pengeluaran untuk kebutuhan pangan sebesar Rp. 17.981.053 dan pengeluaran untuk kebutuhan non pangan yaitu sebesar Rp. 16.273.296. Hasil analisis Indeks Engel ialah 52,49%, artinya total pendapatan nelayan penangkap gurita lebih dari setengah pendapatan digunakan untuk memenuhi kebutuhan pangan saja. Proporsi untuk pangan yaitu 52,49% lebih besar dibanding proporsi untuk non pangan yaitu 47,51%. Hal ini menandakan bahwa taraf hidup atau tingkat kesejahteraan nelayan penangkap gurita di Desa Bulutui masih tergolong rendah. Kata Kunci: taraf hidup, nelayan, gurita, Bulutui